2017
DOI: 10.1002/aoc.3704
|View full text |Cite
|
Sign up to set email alerts
|

Tin(IV) Schiff base complexes derived from pyridoxal: Synthesis, spectroscopic properties and cytotoxicity

Abstract: The synthesis of monomeric pentacoordinated diorganotin(IV) complexes derived from pyridoxal hydrochloride and 4-or 5-R-substituted ortho-aminophenols is described. The complexes were characterized using UV-visible, infrared, mass, 1 H NMR, 13 C NMR and 119 Sn NMR spectral techniques. The molecular structure of three complexes was established using X-ray diffraction: 3b and 3d show a distorted trigonal bipyramidal geometry, in which the basal plane is defined by the butyl groups and the iminic nitrogen atom, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 42 publications
1
6
0
1
Order By: Relevance
“…Schiff bases are a serious category of compounds reported to own nitrogen carbon double bond which is answerable for various biological activities, including anticancer, antipyretic, antitumor, anti‐inflammatory activities . They possess chelatogenic properties, so form interesting ligands in coordination chemistry . Transition metal complexes of hydrazones have many applications such as antibacterial, antifungal, antiviral, and anticancer agents and they are considered as important model for several biological systems .…”
Section: Introductionmentioning
confidence: 99%
“…Schiff bases are a serious category of compounds reported to own nitrogen carbon double bond which is answerable for various biological activities, including anticancer, antipyretic, antitumor, anti‐inflammatory activities . They possess chelatogenic properties, so form interesting ligands in coordination chemistry . Transition metal complexes of hydrazones have many applications such as antibacterial, antifungal, antiviral, and anticancer agents and they are considered as important model for several biological systems .…”
Section: Introductionmentioning
confidence: 99%
“…In the spectra of 1 and 2, the v(OH) was not observed, which suggested that the v(OH) band overlapped with the v(N-H) band due to hydrogen bonding (NH...OH) between the two groups [57,58]. The v (OH) was observed in the calculated spectra because they were generated from the gas phase structures, while experimental spectra were analyzed in the solid state where the compounds are in a more concentrated form, resulting in either intermolecular and/or intramolecular hydrogen bonding similar to that observed in structurally-related Schiff bases [23,59,60].…”
Section: Ftir Analysismentioning
confidence: 93%
“…Кроме того, комплексы, замещенные в положении 8, были более токсичными, чем в положении 9. Более низкая токсичность наблюдалась также для комплексов, которые содержали нитрогруппу и обладали более высокой цитотоксичностью по отношению к клеточным линиям U-251, HCT-15, MCF-7 и SKLU-1 [14].…”
Section: оловоорганические комплексы с N-донорными лигандамиunclassified